Risk Factors for Postoperative Paralytic Ileus in Advanced-age Patients after Laparoscopic Colorectal Surgery: A Retrospective Study of 124 Consecutive Patients - Takaaki Fujimoto; Tatsuya Manabe; Kumpei Yukimoto; Yasuhiro Tsuru; Hiroshi Kitagawa; Keiichiro Okuyama; Shin Takesue; Keita Kai; Hirokazu Noshiro (Journal of the Anus, Rectum and Colon, 2023)
Objectives: Postoperative paralytic ileus (POI) is one of the most common and troublesome complications following colorectal surgery. However, to date, the risk factors for POI remain unclear. This study aimed to identify the risk factors for POI following laparoscopic colorectal surgery in advanced-age patients. Methods: The clinical data of 124 patients aged 75 years who underwent curative colorectal surgery from January 2018 to December 2020 were retrospectively reviewed. The relationship between POI and clinicopathological data including sarcopenia and visceral fat obesity was then assessed. Sarcopenia was defined as a low skeletal muscle mass index; visceral obesity, visceral fat with an area 100 cm2 on computed tomography at the level of the third lumbar vertebra; and sarcobesity, sarcopenia with visceral obesity. Results: The rate of POI was 9% (12/124 patients), and all the affected patients improved with conservative treatment. In the univariate and multivariate analyses, sarcopenia and sarcobesity were significant predictive factors for POI. Conclusions: Sarcopenia and sarcobesity may be risk factors for POI in patients aged 75 years after laparoscopic colorectal surgery.